TREATMENT OF NON-TECHNICAL ELECTRICAL ENERGY LOSSES IN INCOME TAX - Moscoso Laura, Patricia (2025)
Non-technical energy losses impact the profitability of electric utilities and the stability of the energy market; these losses resulting from fraud, illegal connections and administrative errors create regulatory and tax challenges. This study examines the income tax treatment in Peru, Brazil, Colombia and Chile using a qualitative approach based on normative, jurisprudential and doctrinal analysis, along with a comparative review of each country’s tax regulations.The results highlight significant discrepancies with respect to the deductibility of such losses. In Peru, a judicial procedure is required for these losses to be recognized for tax purposes. This leads to legal uncertainty and increases the burden of proof. In Brazil, ANEEL allows some losses to be carried forward to the electricity tariff, but their tax deductibility is subject to specific regulations. Colombia and Chile adopt a more flexible approach, allowing deduction through technical audits and regulatory certifications without requiring a court ruling.The study concludes that the absence of tax harmonization affects the competitiveness of the sector and discourages investment in technologies to mitigate electricity fraud.  It is suggested to implement homogeneous criteria for their deduction, prioritizing technical audits and precise regulations, instead of judicial requirements that are complex to comply with. A more balanced regulatory framework would facilitate the reduction of these losses without jeopardizing the financial sustainability of the electricity sector.  Keywords: Non-technical losses, income tax, electricity sector, tax regulations.